Diversity in Fibroblast Growth Factor Receptor 1 Regulation: Learning from the Investigation of Kallmann Syndrome - Kim, S.-H.; Hu, Y.; Cadman, S.; Bouloux, P. (Journal of neuroendocrinology, 2008)
The unravelling of the genetic basis of the hypogonadotrophic hypogonadal disorders, including Kallmann syndrome (KS), has led to renewed interest into the developmental biology of gonadotrophin‐releasing hormone (GnRH) neurones and, more generally, into the molecular mechanisms of reproduction. KS is characterised by the association of GnRH deficiency with diminished olfaction. Until recently, only two KS‐associated genes were known: KAL1 and KAL2. KAL1 encodes the cell membrane and extracellular matrix‐associated secreted protein anosmin‐1 which is implicated in the X‐linked form of KS. Anosmin‐1 shows high affinity binding to heparan sulphate (HS) and its function remains the focus of ongoing investigation, although a role in axonal guidance and neuronal migration, which are processes essential for normal GnRH ontogeny and olfactory bulb histogenesis, has been suggested. KAL2, identified as the fibroblast growth factor receptor 1 (FGFR1) gene, has now been recognised to be the underlying genetic defect for an autosomal dominant form of KS. The diverse signalling pathways initiated upon FGFR activation can elicit pleiotropic cellular responses depending on the cellular context. Signalling through FGFR requires HS for receptor dimerisation and ligand binding. Current evidence supports a HS‐dependent interaction between anosmin‐1 and FGFR1, where anosmin‐1 serves as a co‐ligand activator enhancing the signal acitivity, the finer details of whose mechanism remain the subject of intense investigation. Recently, mutations in the genes encoding prokineticin 2 (PK2) and prokineticin receptor 2 (PKR2) were reported in a cohort of KS patients, further reinforcing the view of KS as a multigenic trait involving divergent pathways. Here, we review the historical and current understandings of KS and discuss the latest findings from the molecular and cellular studies of the KS‐associated proteins, and describe the evidence that suggests convergence of several of these pathways during normal GnRH and olfactory neuronal ontogeny.